The Effect of Wnt Pathway Modulators on Human iPSC-Derived Pancreatic Beta Cell Maturation - Vethe, Heidrun; Ghila, Luiza; Berle, Magnus; Hoareau, Laurence; Haaland, Øystein A.; Scholz, Hanne; Paulo, Joao A.; Chera, Simona; Ræder, Helge (Frontiers in Endocrinology, 2019)
Current published protocols for targeted differentiation of human stem cells towards pancreatic β-cells fail to deliver sufficiently mature cells with functional properties comparable to human islet β-cells. We aimed to assess whether Wnt-modulation could promote the final protocol stages of β-cell maturation, building our hypothesis on our previous findings of Wnt activation in immature hiPSC-derived S7 cells compared to adult human islets and with recent data reporting a link between Wnt/PCP and in vitro β-cell maturation. In this study, we stimulated hiPSC-derived S7 cells with canonical and non-canonical Wnt signaling pathways with synthetic proteins including WNT3A, WNT4, WNT5A and WNT5B as well as inhibition of endogenous Wnt signaling with the Tankyrase inhibitor G007-LK (TKi). Our data show that neither canonical nor non-canonical Wnt stimulation alone is enough to mature β-cells, however, global proteomics profiling of TKi-treated S7 cells showed more similarity to adult human islets, suggesting that inhibition of endogenous Wnt contribute towards final β-cell maturation.